Barbados. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Barbados during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as agrotourism, financing, nutrition, public policies, protected agriculture, good agricultural practices, costs, training, trade agricultural, veterinary, training and post-harvest techniques. Finally, technical assistance was provided in irrigation, animal feeding, rainwater harvesting, control of pests and diseases, such as tuberculosis, brucellosis, H1N1 influenza and salmonella enteritis, and the value chains of roots, tubers, fruits and vegetables.